Academic freedom: Current perception of university teaching - Gómez Arteta, Indira Iracema (2017)
The research was oriented to interpret the perception that the teachers of the Faculty of Education Sciences of the Universidad Nacional del Altiplano - Puno in 2015 have about the freedom of teaching, identifying the faculties it grants and the limits that restrict their exercise. The research is qualitative and its design is phenomenological, to understand the perceptions of teachers, who constitute the population of analysis, from which an intentional sample of 9 teachers was selected, with 11 to 30 years of permanence in the institution. The axes of analysis are the perception of the faculties it grants and the limits that restrict the freedom of teaching, focusing on the knowledge and behaviors assumed by the teachers in each case. Data were collected using the in-depth interview technique and the in-depth interview guide as an instrument. The results show that the freedom of teaching, in the perception of teachers, is a right and a duty that serves the teacher and the student, considered as the freedom to introduce concepts and themes necessary to contextualize curricular planning and execution, promoting the free work development of the teacher, with respect to the legal framework. The powers it grants are freedom of thought, opinion and action. The limits that restrict it are the norms, political pressure, scientific advance and the opinion of the people.